Cuban Subterranean Termite (proposed), Florida Dampwood Termite (old unofficial name), Prorhinotermes simplex (Hagen) (Insecta: Isoptera: Rhinotermitidae) - Rudolf H. Scheffrahn; Nan-Yao Su; Brian Cabrera; William Kern, Jr. (EDIS)
Prorhinotermes is a tropical genus of some 20 species with the greatest diversity in Southeast Asia. Three species of Prorhinotermes occur in the New World including Prorhinotermes simplex (Hagen). This species is endemic to and known only from southeastern Florida, western Cuba, Jamaica, and Puerto Rico. Species of Prorhinotermes generally live in or near coastal habitats and on islands. This document is EENY-282, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2003.